PERAN PEMEDIASI PRO-ENVIRONMENTAL ATTITUDE PADA PENGARUH INNOVATIVENESS TERHADAP NIAT BELI PRODUK HERBAL - Muhammad Enrico; Rini Kuswati (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study was to analyze the role of pro-environmental attitude mediators on the influence of innovativeness on the purchase intention of herbal products. The type of research used in research uses quantitative methods. The population in this study is the community in Solo Raya. The sampling technique in this study is Non-probability Sampling with purposive sampling techniques. The sample used in this study was 200 respondents. This study used primary data in its preparation. Data were obtained through respondents' answers using a closed type of questionnaire. The data collection method used in this study was by distributing questionnaires. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. The results showed that hedonist innovativeness had a positive and significant effect on purchase intent. Social innovativeness has a positive and significant effect on purchase intent. Hedonist innovativeness has a positive and significant effect on pro-environmental attitudes. Social innovativeness has a positive and significant effect on pro-environmental attitudes. Pro-environmental attitude has a positive and significant effect on purchase intent. Pro-environmental attitudes mediate the influence of hedonist innovativeness on purchase intent, partially. Pro-environmental attitudes mediate the influence of social innovativeness on purchase intent, partially